The paradoxes of interdisciplinarity: The annales, between history and the social sciences (2011)
The analysis in this article emerges from the encounter between a general reflection on the shared epistemology of the Social Sciences and the examination of a specific body of work, in this case a reading of the journal Annales. The article offers a criticism of disciplinary boundaries and explores a contradiction that characterizes the Annales project. On the one hand, the reading affirms that nothing, in principal or practice, allows one to determine the essential area or method of History, Sociology, Anthropology, or Geography as autonomous disciplines. On the other, the authors of the Annales were known for their strong commitment to the discipline of History, and one can conclude that they did little to breakdown disciplinary divisions.